An in-depth review of innovative work behaviour in the hospitality industry - Setiawan, Nyoman Gede Tryadhi Putra; Utami, Hamidah Nayati; Afrianty, Tri Wulida (Universitas Negeri Surabaya, Indonesia, 2024)
Research on innovative work behaviour in the hospitality industry and understanding cross-cultural issues is becoming increasingly essential. This study aims to comprehensively map factors that directly, indirectly, mediate, and moderate innovative work behaviour. Also, it reinforces the concept of cultural influences on innovative work behaviour in the hospitality sector. A systematic literature review with a Scopus and Web of Science database is utilised to furnish a comprehensive overview of research in reputable journals. The paper selection process was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). By analysing 108 articles, this review corroborates the notion that cultural factors influence innovative work behaviour in hospitality. It recommends that tourism companies foster innovative work behaviour to reap benefits such as enhanced competitive advantage and reduced turnover intention. However, companies must consider the synergy between national culture and organisational culture.